Studies on the Pathogenicity of Anaerobes, Especially Prevotella bivia, in a Rat Pyometra Model. Issue 2 (1998) - Mikamo, H.; Kawazoe, K.; Izumi, K.; Watanabe, K.; Ueno, K.; Tamaya, T.
Abstract : Objective: Prevotella bivia is one of the anaerobic bacteria that resides in the flora of the female genital tract. We studied the pathogenicity of P. bivia in a rat pyometra model. Methods: The experimental animial (rat) model of pyometra was developed to investigate the pathogenicity of P. bivia in a rat pyometra model. Results: In the groups inoculated with aerobes alone, the infection rate was 10% (1/10) in the Staphylococcus aureus - or Staphylococcus agalactiae -inoculated group and 20% (2/10) in the Escherichia coli -inoculated group. Infection Was not established in the groups inoculated with anaerobes alone. High infection rates were observed in all the mixed-infection groups. In the S. agalactiae - and Bacteroides fragilis -, S. agalactiae - and P. bivia -, E. coli- and B. fragilis -, and E. coli - and P. biviai - inoculated groups, an infection rate of 100% (10/10) was demonstrated. The efficacy of antibiotics such as flomoxef (FMOX) could be determined using a rat pyometra model. In relation to the alteration of vaginal microbial flora during the menstrual cycle, estrogen increased the growth of P. bivia . Conclusion: Mixture of aerobic bacteria and P. bivia increased the pathogenicity of P. bivia . Estrogen would be useful for raising up the inflammatory change of the uterus in experimental models of genital tract infection due to P. bivia .